Using Substances to Cope With the COVID-19 Pandemic: U.S. National Data at Age 19 Years - Patrick, Megan E.; Parks, Michael J.; Fairlie, Anne M.; Kreski, Noah T.; Keyes, Katherine M.; Miech, Richard (Journal of adolescent health, 2022)
To examine predictors of using substances to cope with the COVID-19 pandemic, including pandemic-related isolation, stress, economic hardship, demographics, and prepandemic substance use. A U.S. national sample (N = 1,244) was followed from the 12th grade in Spring 2019 to Fall 2020 (M = 19.6 years) when young adults were asked about their use of marijuana, vaping, drinking, and other drugs to cope. In Fall 2020, 15.7% reported using marijuana, 8.9% increased vaping, and 8.2% increased drinking to cope with social distancing and isolation. In multivariable analyses controlling for demographics and prepandemic substance use, COVID-related isolation was associated with marijuana use (odds ratio = 1.31, 95% confidence interval = 1.06–1.63) and economic hardship with increased drinking (odds ratio = 1.39, 95% confidence interval = 1.01–1.92). There were few demographic differences. Most (>80%) who reported COVID-related substance use coping used that substance before pandemic. Young people reported using substances to cope with the COVID-19 pandemic, especially if they reported prepandemic use.